The attitude of Black people of Hammanskraal towards Afrikaans and changes in this regard : a sociolinguistic and cultural studies approach - Ohlhoff, Heinrich (Carl Heinrich Friedrich) (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.